PENINGKATAN MOTIVASI DAN KETERAMPILAN SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT (STM) DENGAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) DI KELAS X SMAN 1 KAMPAR - Yustina "; Risa Febri Indriani; Darmadi Ahmad (Biogenesis, 2016)
ABSTRACT  A class action research has been done to the increace motivation and skill students with application of learning models Science Technology Society (SENT) with approaches Natural Roaming Around (JAS) in the class X SMAN 1 Kampar. This research was conducted from April to June 2015. The subjects were students of class X MIA1 semester totaling 34 students, consisting of 8 male students and 26 female students. The parameters in this study is motivation and skill students. The results showed that the motivation and skill students has to increased. On learning motivation of 6.41% was obtained after at cycle I and increased to 10.56% at cycle II. Skills such products LKPD and reports have increased at cycle I is 3.21 predicate B + (Good) and increased to 3.58 predicate A- (Excellent) at cycle II. On average skill products has risen 3.43 predicate B + (Good) at cycle I in the form of Mading three-dimensional (3D) and increased to 3.63 predicate A- (Excellent) at cycle II in the form of Bokashi. Based on the research results, it can be concluded that the application of learning models Science Technology Society (SENT) with approaches Natural Roaming Around (JAS) can be to improve motivation and skill students of biology in the class X MIA1 SMAN 1 Kampar. Keywords: Learning models SENT, JAS approach, Learning Motivation, skill Students.